2022
DOI: 10.1186/s12993-022-00193-5
|View full text |Cite
|
Sign up to set email alerts
|

The shifting role of the cerebellum in executive, emotional and social processing across the lifespan

Abstract: The cerebellum’s anatomical and functional organization and network interactions between the cerebellum and the cerebral cortex and subcortical structures are dynamic across the lifespan. Executive, emotional and social (EES) functions have likewise evolved during human development from contributing to primitive behaviors during infancy and childhood to being able to modulate complex actions in adults. In this review, we address how the importance of the cerebellum in the processing of EES functions might chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…However, Beuriat et al (2022) stated that the importance of the role of the cerebellum in executive functions is particularly crucial in newborns and young children when the EF, motor control and perception are more closely interrelated. The cerebellum due to its important role in motor control and sequencing makes executive functions more reliant on these computational properties that compute spatial distance, motor intent, and assist in the execution of sequences of behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Beuriat et al (2022) stated that the importance of the role of the cerebellum in executive functions is particularly crucial in newborns and young children when the EF, motor control and perception are more closely interrelated. The cerebellum due to its important role in motor control and sequencing makes executive functions more reliant on these computational properties that compute spatial distance, motor intent, and assist in the execution of sequences of behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…There is far less research in children concerning the role of the cerebellar lesions in executive functioning (Steinlin et al, 2003;Koustenis et al, 2016;Albazron et al, 2019). As shown by the Beuriat and colleagues (Beuriat et al, 2022), the role of the cerebellum in the regulation of executive, emotional and social factors is changing across lifespan. As a result of anatomical and functional changes, neuroimaging and clinical data indicate that the importance of the role of the cerebellum in human executive functions-related networks shifts from being crucial in newborns and young children to being only supportive in adult life.…”
Section: Introductionmentioning
confidence: 99%
“…Tumors in the occipital lobe can cause blindness, blurred vision, and hallucinations (Hense et al, 2021). Cerebellar tumors affect the ability to coordinate voluntary movements such as balance and blinking whereas brain stem tumors are responsible for disorders of many functions, including basic ones, such as paresis of the limbs, speaking, swallowing, breathing or seeing (Reyes-Botero et al, 2012;Beuriat et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Although symptomatic posterior fossa tumors are typically resected, it has been reported that posterior fossa surgery may have a critical impact on the sensorimotor and cognitive outcomes of children. 14,15 The current management of brain tumors in children is evolving due to an improved understanding of the molecular mechanisms, even though biomarkers are lacking. The complementary information provided by PET and MRI, for example, SUV and ADC, could improve tumor characterization and, indirectly, the use of molecular targeted therapies.…”
mentioning
confidence: 99%
“…Although symptomatic posterior fossa tumors are typically resected, it has been reported that posterior fossa surgery may have a critical impact on the sensorimotor and cognitive outcomes of children 14,15 . The current management of brain tumors in children is evolving due to an improved understanding of the molecular mechanisms, even though biomarkers are lacking.…”
mentioning
confidence: 99%